UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN COOPERATIVE LEARNING MODEL JIGSAW DI SMP NEGERI 1 KIBIN - Sujai, Ahmad (STAI Darul Qalam Tangerang, 2023)
The purpose of this study is to improve student activity and learning outcomes towards the basic concepts and competencies of the lesson through Cooperative Learning Jigsaw, about the law of mad reading in grade 8. The method used in this study is a qualitative method. The subject of the study was a grade 8.E student To carry out the learning above, is to use the Cooperative Learning Model Jigsaw. Through jigsaw model learning, it is hoped that